High School Type as a Predictor of Student Academic Performance and Retention: A Case Study of Student Academic Performance and Retention in relation to High School type qualification in Undergraduate Business Program at an Off-Shore Campus in U.A.E - Larik, Irfan Ali (2016)
It has been observed that students from different high school types tend to show a difference in their academic performance after joining a program of study at a college or a university. The present research attempted to study the relation between student grades in two high school types as a predictor of academic performance in college/university. The findings indicate that several reasons can be attributed for causing the difference in academic performance of students due to the high school type such as school environment, role of peers, gender differences and number of hours of study required and so on. The study indicates a strong positive correlation between the prequalification marks of Intermediate/HSSC students and the total of GPA of the 4 courses (r2 value is 0.492). Though the correlation is positive in the case of GED Students (r2 value is 0.221) but with a lot of variation. In the case of Intermediate/HSSC students not only the correlation r values is strong in comparison with GED students, but also they are clustered close within the range 7.75 and 14.5. So it is apparent that the positive trend that’s seen in intermediate students are more stronger and uniform than in GED students, this is due to their strong foundation in intermediate studies. However the findings would have been more significant with a bigger sample size. The academic performance of students enrolling in the business program after completing Intermediate/HSSC shows a more stable trend as compared to students joining the undergraduate business program after completing their GED.